A role for maternal β-catenin in early mesoderm induction in Xenopus - Schohl, Anne (Oxford University Press, 2003)
Mesoderm formation results from an inducing process that requires maternal and zygotic FGF/MAPK and TGFβ activities, while maternal activation of the Wnt/β-catenin pathway determines the anterior–dorsal axis. Here, we show a new role of Wnt/β-catenin signaling in mesoderm induction. We find that maternal β-catenin signaling is not only active dorsally but also all around the equatorial region, coinciding with the prospective mesoderm. Maternal β-catenin function is required both for expression of dorsal genes and for activation of MAPK and the mesodermal markers Xbra and eomesodermin. β-catenin acts in a non- cell-autonomous manner upstream of zygotic FGF and nodal signals. The Wnt/β-catenin activity in the equatorial region of the early embryo is the first example of a maternally provided mesoderm inducer restricted to the prospective mesoderm.